Properties of multiple Lewis acid sites in alkali metal-exchanged chabazites probed by CO adsorption - Halamek, Jakub; Bulánek, Roman; Rubeš, Miroslav; Bludsky, Ota (Elsevier Science BV, 2024)
Carbon monoxide adsorption on alkali -metal exchanged chabazites (M- CHA , where M = Li, Na, K) was investigated across various Si/Al ratios. The study reveals significant insights into the adsorption behavior, including the persistence of cationic preferences with decreasing Si/Al ratios and the existence of multiple -center interactions involving alkali -metal cations and CO. Results show that for high -silica MCHA zeolites, CO adsorption is effectively described by single and dual adsorption site models, with cation preferences varying by type. In low -silica zeolites, cation positions are primarily influenced by the aluminum distribution and Coulombic interactions. However, the propensity for single -site cation positions (Si/Al ->infinity ) is preserved to a certain degree. The most noticeable example is the small difference between SIII ' occupancies (cations in 8 -membered ring windows) in Na- CHA -2 and K- CHA -2 (0.80 vs. 0.85) that strongly influences the rate of diffusion of CO in the MCHA -2 samples. While FT-IR spectra of high -silica zeolites can be accurately described using cation site stabilities, interaction energies, and CO stretching frequencies, predicting spectra of low -silica chabazites requires a statistical approach and/or molecular dynamics simulations at the DFT level. The findings demonstrate that the dynamical behavior of adsorbates changes dramatically between different alkali metal -exchanged chabazites, highlighting the complex nature of CO adsorption at multiple Lewis acid sites.
Vlastnosti Lewisových kyselých center v iontově vyměněných chabazitech testované pomocí CO adsorpce
Keywords: Adsorption; Lewis acid sites; Alkali metal; Chabazite; Carbon monoxide; FT-IR; Calorimetry; ab initio modeling; Lewisova kyselá centra; iontově vyměněné; chabazit; CO adsorpce